Vigor Benih Kedelai (Glycine max L. Merr) Kultivar Argomulyo dan Dega 1 pada Kondisi Cekaman Salinitas - Kadapi, Muhamad; Sunarso, Cipto; Suminar, Erni (Agrotrop : Journal on Agriculture Science, 2025)
Vigor of Soybean Seed ( Glycine max L. Merr) Cultivars Argomulyo and Dega 1 under Salinity Stress Condition. One of the impacts of climate change is global warming that causes an increasing saline area. This condition became a constraint in the extensification program for soybeans in Indonesia. Salinity at a certain level can inhibit in each stage the growth and development of soybean plants, including the germination stage. Therefore, it is necessary to reveal seed vigor traits of new improved cultivars that have the potential such as high yield and early harvesting under salinity conditions. In this study Dega 1cv. as known early harvesting cultivar was used with Argomulyo as control. This research was carried out from January to March 2024 at the Seed Technology Laboratory, Faculty of Agriculture, Universitas Padjadjaran used two cultivars that were replicated four times and triplet for each unit. The F test at a 5% significance level was used to determine the significance variance between two population cultivars. The Duncan test was used, if there was significance between two populations at a significance level of 5% and t-student test was used to compare between control and saline condition in germination percentage, speed rate of germination, length of root and salinity index. The results showed that genetics may contribute to tolerance on salinity stress as shown in germination percentage, speed rate of germination, length of root and salinity index which showed there were no significant differences between two cultivars in control condition. While the significant difference between two cultivars was in salinity stress condition at 4 dS/m level. Furthermore, Argomulyo and Dega 1 cvs. were classified as tolerance cultivars according to the susceptibility stress index that have values 0.2 and 0.4 respectively.